Defined characteristics of the nursing diagnoses ineffective airway clearanceand ineffective breathing pattern in asthmatic children - Uily Antunes Silveira; Luisa Helena de Oliveira Lima; Marcos Venícios de Oliveira Lopes (Rev Rene)
A cross-sectional study, performed with 42 children who were hospitalized with medical diagnosis of asthma, in an infantile public hospital of Fortaleza – CE. It was developed with the aim of analyzing the accuracy of the defi ned characteristics of the nursing diagnoses “Ineffective airway clearance – IAC” and “Ineffective breathing pattern – IBP” in asthmatic children. For the Ineffective breathing pattern they identifi ed as sensible defi ned characteristics the dyspnea, orthopnea and increased respiratory/ minute frequency. The characteristics of greater specifi city that were presented for such diagnosis was beating of nose wing and increased respiratory/minute frequency. Regarding the diagnosis Ineffective airway clearance, only one characteristic was sensitive: “adventitious breathing noises”. It was so concluded that asthmatic children show defi ned characteristics with are common to a respiratory nursing diagnoses group and not very specifi c of the human responses hereby studied.